Spinco Model 141 Gradient Pump
Used to generate and pump gradients in combination with centrifuges and ultracentrifuges.
Keywords: Medical laboratories--Equipment and supplies; Beckman Instruments, Inc. Spinco Division; Scientific apparatus and instruments; Centrifuges; Beckman Instruments, Inc.